Thyroid follicular carcinoma in a teenager: A case report - Oka, Kosuke (J Gen Fam Med, 2018)
A 19‐year‐old girl complained of an enlarged cervical mass. Based on clinical and cytological assessments, it was diagnosed as thyroid follicular carcinoma and left thyroidectomy was performed. Although thyroid neoplasms are rare in young people, differentiation is needed when the rapid growth of a goiter is detected.